Teachers’ perceptions and readiness toward the implementation of virtual learning environment - Ana Haziqah A Rashid; Nurbiha A Shukor; Zaidatun Tasir; Kew Si Na (Institute of Advanced Engineering and Science, 2021)
The current trend of education is towards the implementation of technology in teaching in order to attract the attention of 21st century learners whereby teachers need to adopt technology-enhanced environment such as the Virtual Learning Environment (VLE) in their teaching. This study aims to investigate the teachers’ perceptions and tendency to use VLE as a tool for teaching. The teachers’ perceptions were investigated based on the main constructs of the Technology Acceptance Model (TAM). The respondents were 178 teachers in southern state of Malaysia. The data were collected using a questionnaire and it is validated through the use of Rasch model. The finding was found that the teachers were moderately ready to use VLE and they moderately accepted the implementation of the VLE (mean=3.67 and 3.65). Besides that, the teachers felt that the VLE was useful (mean=3.58) and was easy to use (mean=3.34). It was also found that 84.2% of the teachers’ acceptance was influenced by the teachers’ readiness, and the teachers’ perceptions of the usefulness and ease of using the VLE in teaching. Therefore, it can be concluded that Malaysian teachers has intention to use VLE in their teaching. The use of VLE can improve the innovative way of teaching that can increase students’ interest in constructing knowledge through their learning process.